The three billy goats Gruff - Asbjornsen, Peter Christen, 1812-1885.; Moe, Jorgen Engebretsen, 1813-1882.; Brown, Marcia (San Diego : Harcourt Brace Jovanovich, 1991)
The three billy goats outsmart the hungry troll who lives under the bridge.
Translation of: Tre bukkene Bruse.
"Voyager books"--Cover.
Horn Book Magazine
K-3
Keywords: Fairy tales; Folklore -- Norway; Fairy tales; Folklore -- Norway